Pkm Sosialisasi Pemanfaatan Aplikasi Flip Di Cynara's Corner - Rahmatika Rahmatika; Ulfa Pauziah; Ega Shela Marsiani (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Each of our online transactions requires a money transfer transaction to carry out these activities. Of the various banks available, it costs a lot of money to pay different bank admins. For that we need an application that can help online buying and selling transactions so that business actors do not experience losses to pay bank admins. The existing technology that is already in great demand by business actors is the Flip application. In addition, Flip not only offers free interbank transfer fees, but there are many others such as refunds, buy credit, top up data packages, electricity tokens and others. However, there are still many who do not know and do not understand what the advantages of the Flip application are. Therefore, we will conduct a socialization on the utilization and use of the Flip application where from this socialization it can be used by business actors of children's clothing agents Cynara's Corner for resellers transacting in online buying and selling, and can help resellers to reduce admin transaction costs between banks, so that profits the maximum is obtained.